Optimalisasi Teknologi Fog Harvesting: Studi Performa Fog Collector Model Savonius dan Datar - Jamaldi, Agus; Supriyanto, Agung; Prihastomo, Arik; Davantio, Jeremy Adi (Rekayasa, 2025)
Fog harvesting or fog catching is a technological breakthrough used as a sustainable and environmentally friendly water source. This technology utilizes mist converted into water droplets captured by the fog collector. This study was conducted to analyze the effectiveness of the number and shape of fog collectors in a fog harvesting prototype. The shape of the fog collector used is flat and semicircular (savonius). The variation in the number of fog collectors used is 2, 4, and 6 pieces. The fog collector material is High-Density Polyethylene (HDPE) with Rectangular and Raschel mesh. The area of flat and semicircular fog collectors (Savonius) is 209.25 and 310.5 cm2, with a shading coefficient of 60%, respectively. The data collection method is carried out by blowing the mist generated by the ultrasonic mist maker to the fog collector using a blower for 1 hour. The water mass amount that can be absorbed by the fog collector is obtained by weighing it every 15 minutes. The results showed that the more fog collectors, the more water mass was produced. The difference in the type of fog collector mesh also affects the amount of water mass produced. The semicircular type (Savonius) produces more water mass from fog than the flat type. The experiment results showed that the semicircular type (Savonius) with 6 fog collectors with the Raschel mesh type produced the most water mass of 6.27 grams. Based on the results, the semicircular fog collector (Savonius) with the Raschel mesh type is more effective than the flat type.